Student Perceptions of the Implementation of the Concept of Organizer Teacher and Freedom in Learning in Earth and Space Science (ESS) Lectures - Ahmad Farhan; Elisa; Fitria Herliana; Sri Wahyuni; Evita Kharisma (Jurnal Penelitian Pendidikan IPA, 2023)
The research was conducted to collect students’ perceptions about lecturers' competence in implementing the course, student activity, and atmosphere of course, students' ability to hold material of learning in earth and space science. The research method used was quasi-experimental. The research was carried out in 2 steps where the first step was the control stage carried out using the discussion method. The next step was the treatment stage carried out using innovative discussion methods. The final step gave students the freedom to ask questions about the material earth and space science that they want to know. Student perceptions were obtained using a questionnaire instrument. The results of data analysis in this study show that the quality of lecturers' abilities in managing lectures is in the good category for the control stage and very good for the treatment stage, the lecture atmosphere is pleasant (control) and very pleasant (treatment), students feel active (control), and very active (treatment) in lectures, students' ability to hold a lot of course material (control) and very much (treatment). It was concluded that the innovative discussion method in earth and space science course was able to improve the quality of the lecture process.